2013
DOI: 10.1007/s12022-013-9238-y
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for On-Site Evaluation of Thyroid Fine Needle Aspiration to Reduce the Nondiagnostic Rate?

Abstract: The use of immediate on-site evaluation of fine-needle aspiration biopsy (FNAB) specimens can determine the adequacy of specimens and provides a specific preliminary diagnosis. In this prospective study, we evaluated the impact of on-site assessment of thyroid FNAB performed under ultrasound guidance. Totally, 204 (170 female, 34 male) patients (102 on site, 102 control group) were included. The patients were randomized on site and regular cytologic examination groups. Quick May-Grünwald Giemsa stain was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…Therefore, efforts should be made to optimize specimen handling and adequacy. In the current study, the implementation of ROSE significantly increased the percentage of nodules deemed adequate for analysis in the final cytology report, with a final ND rate of only 6.6% in the ROSE group, a finding that is comparable to several experiences reported in the literature . Unfortunately, no review of ND cases among the ROSE group was performed, and a clear cause of unsatisfactory results could not be determined from the collected data.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, efforts should be made to optimize specimen handling and adequacy. In the current study, the implementation of ROSE significantly increased the percentage of nodules deemed adequate for analysis in the final cytology report, with a final ND rate of only 6.6% in the ROSE group, a finding that is comparable to several experiences reported in the literature . Unfortunately, no review of ND cases among the ROSE group was performed, and a clear cause of unsatisfactory results could not be determined from the collected data.…”
Section: Discussionsupporting
confidence: 73%
“…However, the impact of ROSE on thyroid FNAB has been a matter of debate. Although some authors have reported a significant increase in specimen adequacy and a decrease in the mean number of needle passes required with ROSE, others have advocated that its benefits are limited, with extended procedure times and higher costs . In the current study, we retrospectively reviewed all thyroid FNABs performed in our service within the last 2 years to assess the impact of the incorporation of ROSE on the overall management, adequacy rate, and final diagnosis of the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate assessment of the sample for adequacy by biomedical scientists or pathologists at the time of aspiration can reduce the rate of unsatisfactory samples and be cost‐effective especially if the underlying adequacy rate is low , and facilitate collection of material for ancillary tests.…”
Section: Chaptermentioning
confidence: 99%
“…The overall ND rate in the post‐thyroid service group was relatively high compared with the literature (2–24%) . In 2016, our thyroid service had a clear reduction in ND rates, from 13.9% in 2015 to 6.1%.…”
Section: Discussionmentioning
confidence: 57%
“…Factors that influence sample adequacy include nodule characteristics (size, cystic versus solid, cellularity, vascularity and fibrosis), experience level of operators and cytopathologists, procedural variations (slide preparation, fixation and staining techniques; number of needle passes, size of needle gauge and aspiration versus non‐aspiration sampling techniques), and the presence of on‐site cytology assessment for sample adequacy . Studies have shown that on‐site cytology can reduce the ND rates of US‐guided FNAs …”
Section: Introductionmentioning
confidence: 99%